Antioxidant and Anti-Tumor Effects of Dietary Vitamins A, C, and E - Alexander J. Didier; Jennifer Stiene; Lauren Fang; Dean Watkins; Lance D. Dworkin; Justin F. Creeden (MDPI AG, 2023)
Oxidative stress, a condition characterized by an imbalance between pro-oxidant molecules and antioxidant defense systems, is increasingly recognized as a key contributor to cancer development. This is because the reactive oxygen species (ROS) generated during oxidative stress can damage DNA, proteins, and lipids to facilitate mutations and other cellular changes that promote cancer growth. Antioxidant supplementation is a potential strategy for decreasing cancer incidence; by reducing oxidative stress, DNA damage and other deleterious cellular changes may be attenuated. Several clinical trials have been conducted to investigate the role of antioxidant supplements in cancer prevention. Some studies have found that antioxidant supplements, such as vitamin A, vitamin C, and vitamin E, can reduce the risk of certain types of cancer. On the other hand, some studies posit an increased risk of cancer with antioxidant supplement use. In this review, we will provide an overview of the current understanding of the role of oxidative stress in cancer formation, as well as the potential benefits of antioxidant supplementation in cancer prevention. Additionally, we will discuss both preclinical and clinical studies highlighting the potentials and limitations of preventive antioxidant strategies.